Suitability of assessing population-level impacts from construction of a single wind farm – a case study on North Sea harbour porpoises - van Geel, N. C. F.; Benjamins, S.; Marmo, B.; Nabe-Nielsen, J.; Wittich, A.; Risch, D.; Todd, V. L. G.; Wilson, B. (Frontiers in Marine Science, 2025)
Continued development of offshore renewable energy is urgently needed to support the goal of achieving global Net Zero targets; however, concerns persist about impacts of construction noise on acoustically sensitive species such as the harbour porpoise (Phocoena phocoena). Population impact modelling frameworks have been proposed as a quantitative way to evaluate whether disturbance, as experienced by individual animals, might result in negative population-level consequences, and suggested as useful tools in support of Environmental Impact Assessments. However, questions remain regarding model applicability to projects of different spatial scales. This study applied two such models (iPCoD and DEPONS) to assess potential population-level impacts of construction of the East Anglia ONE wind farm on North Sea harbour porpoises. Both models were parameterised using project-specific input values underpinned by static passive acoustic monitoring data. The various iPCoD and DEPONS scenario simulations did not predict any long-term population-level impacts in response to pin-piling activities. This is likely due to discrepancy in scale between localised, short-term impacts of constructing a single wind farm in comparison to the range of the North Sea porpoise population. DEPONS modelling also revealed no long-term negative impact of pin-piling on predicted porpoise numbers within the boundary of the Southern North Sea Special Area of Conservation. Current results highlight the importance of scale when using either modelling framework to evaluate the likelihood of long-term population-level impacts on abundant, wide-ranging species from individual offshore renewables developments. Cumulative population effects from human activities, including other construction projects, commercial shipping, hydrocarbon exploitation, and fisheries bycatch, are not well understood but can be approached with the modelling frameworks explored here. However, such effects will not be apparent when applying these models to individual construction projects and in isolation from coexisting pressures. There is a risk that ignoring co-occurring pressures may result in an incomplete picture of simulated population trajectories that should be considered carefully when these models are proposed to evaluate impacts of offshore renewable construction projects. We advocate that long-term population impact modelling should be applied on a regional basis and take additional wind farm developments as well as other cumulative pressures into consideration.